Analisis Rasio Kesehatan Kinerja Keuangan pada Koppontren Al Mubarok Lekok Kabupaten Pasuruan - Abdussalam, Abdussalam; Ihsan, Moh.; Hidayatullah, Syarif (Journal of Islamic Finance and Syariah Banking, 2024)
This study aims to analyze the health of financial ratios in Koppontren Al Mubarok, Lekok District, Pasuruan, East Java. The methodological approach used in this research is descriptive-quantitative, using secondary data in the form of financial statements for 5 years. The analysis method used is the analysis of the health of financial performance ratios, namely the ratios of liquidity, solvency, efficiency, and profitability. The results showed that Koppontren Al Mubarok Lekok’s financial ratios were categorized as not good (unhealthy). This is indicated by the liquidity ratios (current ratio and cash ratio) and solvency ratios (debt to equity ratio and debt to asset ratio), on average, since the last 5 years from 2018–2022, are in the category of not good or unhealthy, while the efficiency ratio (Bopo) and profitability ratios (net profit margin, return on assets, and return on equity) are in the category of excellent, as referred to in the standards outlined in the Regulation of the Minister of Cooperatives and Small and Medium Enterprises (SMEs) Regulation No.06/Per/M.KUKM/V/2006 concerning health assessment of reward cooperatives.